2017
DOI: 10.1111/opo.12371
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of stereo thresholds by the TNO stereotest is not due to global stereopsis

Abstract: PurposeIt has been repeatedly shown that the TNO stereotest overestimates stereo threshold compared to other clinical stereotests. In the current study, we test whether this overestimation can be attributed to a distinction between ‘global’ (or ‘cyclopean’) and ‘local’ (feature or contour‐based) stereopsis.MethodsWe compared stereo thresholds of a global (TNO) and a local clinical stereotest (Randot Circles). In addition, a global and a local psychophysical stereotest were added to the design. One hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 47 publications
3
35
0
2
Order By: Relevance
“…Clearly, an ideal test would avoid non-stereo artefacts, such as the motion artefacts visible monocularly in both the Frisby and Lang stereotests if the patient moves their head. It also seems desirable to avoid the interocular colour differences introduced with anaglyph glasses, which may be responsible for the poorer stereo thresholds obtained with the TNO stereotest (Vancleef et al, 2017). However, the question of which stereotest is "best" is complicated by the fact that, as indicated in the Introduction, different tests measure different aspects of stereopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, an ideal test would avoid non-stereo artefacts, such as the motion artefacts visible monocularly in both the Frisby and Lang stereotests if the patient moves their head. It also seems desirable to avoid the interocular colour differences introduced with anaglyph glasses, which may be responsible for the poorer stereo thresholds obtained with the TNO stereotest (Vancleef et al, 2017). However, the question of which stereotest is "best" is complicated by the fact that, as indicated in the Introduction, different tests measure different aspects of stereopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular motility was tested with a penlight, and binocular function was tested with the TNO test (Vancleef et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy may be caused by the measurement tool, because the TNO stereotest was found to overestimate the stereo thresholds compared to the randot stereotest. 24 Additionally, the severity of the conditions of the patients included 50 per cent mild and 50 per cent severe TBI in this study (as shown in Table 1) which may explain the elevated stereoacuity thresholds. 22 Nevertheless, all the studies reported elevated stereoacuity thresholds in TBI patients compared with control subjects.…”
Section: Table 2 Comparison Of Accommodation Function Values Betweenmentioning
confidence: 95%
“…Near stereoacuity was assessed using the TNO stereopsis test (Lameris Ootech BV Ede, 18th edition), previously described. 24 ACCOMMODATION TESTS Amplitude of accommodation was measured monocularly and binocularly using the Push-Up method. Expected amplitude of accommodation was calculated according to the Hofstetter formula.…”
Section: Stereopsismentioning
confidence: 99%